Persepsi Pengguna Pada SIMRS Medify Berdasarkan Model DeLone dan McLean - Agsari, Ardisa Lintang; Budi, Savitri Citra; Azizah, Delia Nur; Aulia, Farida Zulfi; Antika, Tabita; Palimirmaningtyas, Titah Winengku; Natalia, Dewi (Politeknik Negeri Jember, 2024)
The advancement of information technology has driven a new paradigm in healthcare service delivery. The implementation of Medify as a new Hospital Management Information System (SIMRS) at RSUD Wates is a response to government regulations regarding health data management and digital transformation in Indonesia. This study aims to analyze user perceptions of the Medify SIMRS. This research is descriptive with a quantitative approach. Data collection was carried out through interviews, observations, and questionnaires. The questionnaire guide uses the DeLone and McLean analysis model, which includes six variables. The study population involved medical record officers at RSUD Wates and other healthcare workers using medical records at the hospital. The study found that the highest user perception percentages were on six aspects: system quality at 50,0%, information quality at 51,5%, service quality at 49,2%, perceived satisfaction at 53.0%, perceived usefulness of the system at 41,7%, and system benefits at 53,8%. Most respondents agreed that the Medify SIMRS is implemented and used for services. The highest evaluation score interpretation was in the aspect of system quality and perceived satisfaction, with a value of 72.1%, which falls into the Good criteria.